Comparative evaluation of the efficacy of Triphala mouthwash and Curcumin mouthwash in the treatment of gingivitis – A randomized controlled study - S. Divya Bharathi; S.P. Aiswarya; Archana R. Sankar (Journal of Oral Biology and Craniofacial Research)
Background: Numerous studies on Triphala and Curcumin mouthwashes were analyzed individually and no study has compared the efficacy of Triphala mouthwash to Curcumin mouthwash in the management of gingivitis. Although various mouthwashes have shown reduction of plaque and gingivitis the search is still on for an ideal mouthwash with minimum side effects and better patient acceptance. Objectives: To access the efficacy of all the mouthwashes in the management of gingivitis. Methods: By purposive sampling, 81 patients of both sexes with gingivitis were randomized by lottery method into 3 groups - A, B and C. Group A received scaling and Triphala mouthwash, Group B received scaling and Curcumin mouthwash and Group C underwent scaling and received Chlorhexidine mouthwash. Oral hygiene was assessed using Plaque, Gingival and Bleeding indices at baseline,7th day and 14th day. The inter-group comparisons were analysed using One-way analysis of variance (ANOVA) and multiple comparisons using Tukey's Honest significant difference test (α = 0.05) and the intra-group comparisons for the indices across various time periods within each group were analysed using Repeated-measures ANOVA and Bonferroni-adjusted pairwise comparisons post hoc test (α = 0.05). The statistical significance was set at p ≤ 0.05. Results: The study has shown that herbal mouthwashes are as effective as chlorhexidine in treating gingivitis although curcumin mouthwash showed a greater potential in reducing gingival inflammation. Conclusion: Both Triphala and Curcumin mouthwashes were proven to be equally effective in reducing plaque, gingival and bleeding scores, although curcumin was better in reducing gingival inflammation. Hence herbal mouthwashes such as Triphala and Curcumin with no side effects can be considered as an alternative mouthwash to chlorhexidine.